A comprehensive evaluation on pyrolysis kinetics, thermodynamics, product properties and formation pathways of jatropha oil for high-value utilization. (1st April 2022) - Dong, Ruihan; Chen, Fangjun; Zhang, Fengxia; Yang, Shiliang; Liu, Huili; Wang, Hua; Hu, Jianhang
Graphical abstract: Highlights: Pyrolysis experiments of jatropha oil were performed by TGA and down tube reactor. Kinetic triplets of jatropha oil pyrolysis were studied. High temperature promoted the secondary cracking of pyrolysis products. Reaction control mechanism was order of reaction with the order of 1.5. Reaction pathways of major volatiles during fast pyrolysis of jatropha oil inferred. Abstract: Accurately understanding the pyrolysis kinetics, thermodynamics, product properties and formation pathways of jatropha oil (JO) is crucial to achieve its high-value utilization. In this study, the kinetic triplets of JO pyrolysis were comprehensively investigated using the iso -conversional, and model-fitting methods based on thermogravimetric experiments. The results demonstrated that the apparent activation energy of JO pyrolysis was 188.95–238.71 kJ/mol; the range of variation of pre-exponential factor was 6.5 × 10 13 –5.3 × 10 16 s −1 ; the reaction control mechanism was the order of reaction model with an order of 1.5. The high heating value (40.97 MJ/kg), enthalpy change (183.74–231.33 kJ/mol) and Gibbs free energy (179.01–180.12 kJ/mol) indicated the significant potential of JO as bioenergy. The liquid products were mainly composed of, olefins, aromatics, alcohols, alkanes, aldehydes, ketones, acids, and esters. High temperature promoted the secondary cracking of pyrolysis products and produced more gas products. The reaction pathways of the major volatiles during the fast pyrolysis of JO were proposed based on the composition of the pyrolysis products. The results benefit for the operation and optimization of pyrolysis reactors.